2021
DOI: 10.4240/wjgs.v13.i10.1149
|View full text |Cite
|
Sign up to set email alerts
|

Transanal minimally invasive surgery using laparoscopic instruments of the rectum: A review

Abstract: Transanal minimally invasive surgery (TAMIS) was first described in 2010 as an alternative to transanal endoscopic microsurgery (TEM). The TAMIS technique can be access to the proximal and mid-rectum for resection of benign and early-stage malignant rectal lesions and also used for noncurative intent surgery of more advanced lesions in patients who are not candidates for radical surgery. TAMIS has a shorter learning curve, reduced device setup time, flexibility in instrument use, and versatility in application… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
1
8

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 71 publications
0
23
1
8
Order By: Relevance
“…The peritoneal violations that occurred, happened all ≤ 12 cm from the anal verge. When comparing peritoneal violation, the present review identified seven cases (2.1%) while Kim et al [ 38 ] found peritoneal entry in 6.0% of the L-TAMIS procedures. The studies with peritoneal entry complications were all in the setting of full thickness excisions [ 34 ].…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…The peritoneal violations that occurred, happened all ≤ 12 cm from the anal verge. When comparing peritoneal violation, the present review identified seven cases (2.1%) while Kim et al [ 38 ] found peritoneal entry in 6.0% of the L-TAMIS procedures. The studies with peritoneal entry complications were all in the setting of full thickness excisions [ 34 ].…”
Section: Discussionmentioning
confidence: 65%
“…When evaluating the number of complications for patients undergoing R-TAMIS, 10.5% suffered from complications. A large L-TAMIS series of 200 cases by Lee et al [ 37 ] found a complication rate of 7%, and a recent published review on L-TAMIS with more than 1200 cases reported a complication rate of 18.4% [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent review on TAMIS and other transanal and intraluminal approach reported a shorter operative time for TAMIS, while recurrence rate, complication, and quality of life are similar to those of TEM. 21…”
Section: Transanal Endoscopic Microsurgerymentioning
confidence: 99%
“…E cikknek nem célja a TAMIS-technikának a hagyományos transanalis nyílt excisióval szembeni előnyeinek részletezése, elég legyen itt tényként megfogalmazni, hogy az analis csatorna felső széle felé terjedő, azaz rectum polypok esetében a TEM/TAMIS technika minden minőségi mutatóban előnyösebb és így kötelezően választandó eljárás a TAE-val szemben! [14] (Ugyanígy elmondható, hogy az endoscopos mucosa resectio, EMR technikáját mind "en block" arány, mind R0 arány és ezek alapján a lokális kiújulás (LR) arány vonatkozásában is felülmúlja az endoscopos submucosus dissectio (ESD) [15].…”
Section: Endoscopia éS Sebészet Szerepe a Rectum Polypok Kezelésébenunclassified